A structural equation model analysis of phosphorus transformations in global unfertilized and uncultivated soils. Issue 9 (17th September 2016) - Hou, Enqing; Chen, Chengrong; Kuang, Yuanwen; Zhang, Yuguang; Heenan, Marijke; Wen, Dazhi
Abstract: Understanding the soil phosphorus (P) cycle is a prerequisite for predicting how environmental changes may influence the dynamics and availability of P in soil. We compiled a database of P fractions sequentially extracted by the Hedley procedure and its modification in 626 unfertilized and uncultivated soils worldwide. With this database, we applied structural equation modeling to test hypothetical soil P transformation models and to quantify the importance of different soil P pools and P transformation pathways in shaping soil P availability at a global scale. Our models revealed that soluble inorganic P (Pi, a readily available P pool) was positively and directly influenced by labile Pi, labile organic P (Po), and primary mineral P and negatively and directly influenced by secondary mineral P; soluble Pi was not directly influenced by moderately labile Po or occluded P. The overall effect on soluble Pi was greatest for labile Pi followed by the organic P pools, occluded P, and then primary mineral P; the overall influence from secondary mineral P was small. Labile Pi was directly linked to all other soil P pools and was more strongly linked than soluble Pi to labile Po and primary mineral P. Our study highlights the important roles of labile Pi in mediating P transformations and in determining overall P availability in soils throughout the world. Key Points: A soil P transformation model is proposed to fit a database of P fractions from worldwide soils Soluble inorganic P was directly influenced by labile P, secondary mineral P, and primary mineral P Labile inorganic P mediates most soil P transformations and determines soil P availability